Research Advance on the Sensing Characteristics of Refractive Index Sensors Based on Electromagnetic Metamaterials. (20th July 2021) - Wang, Zongli; Wang, Xin; Wang, Junlin
Abstract : Among different sensing platforms, metamaterials composed of subwavelength or deep subwavelength sized metal resonance elements arrays that are etched on semiconductor substrates or dielectric substrates exhibit excellent characteristics due to the strong localization and enhancement of resonance electromagnetic fields. As a new type of detection method, metamaterial sensors can break through the resolution limit of traditional sensors for a small amount of substance and have the advantages of high sensitivity, fast response, and simple measurement. Significant enhancement of the sensing characteristics of metamaterial sensors was realized by optimizing microstructures (single split-ring, double split-ring, nested split-ring, asymmetric split-ring, three-dimensional split-ring, etc.), using ultrathin substrates or low-index substrate materials, etching away local substrate, and integrating microfluidic channel, etc. This paper mainly reviews the research advance on the improvement of sensing characteristics from optimizing resonance structures and changing substrate materials and morphology. Furthermore, the sensing mechanism and main characteristic parameters of metamaterial sensors are introduced in detail, and the development trend and challenge of metamaterial sensing applications are prospected. It is believed that metamaterial sensors will have potential broader application prospects in environmental monitoring, food safety control, and biosensing in the future.